2019
DOI: 10.1002/adom.201900923
|View full text |Cite
|
Sign up to set email alerts
|

Scaling and Reflection Behaviors of Polaritons in Low‐Dimensional Materials

Abstract: Polaritons in low‐dimensional materials have shown their unique capabilities to concentrate light at the deep subwavelength scale. They behave quite differently from those in conventional metals. On the one hand, the strongly confined polaritons exhibit a large tunability in wavelength following different scaling behaviors in different systems. On the other hand, they show novel reflection behaviors when they encounter topographic boundaries or electronic discontinuities. Here, recent progress on the scaling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 95 publications
(129 reference statements)
0
5
0
Order By: Relevance
“…Reflection and scattering of a surface plasmon from discontinuities in the graphene plane-including the reflection from the edge of a graphene stripe-has already been studied in detail and reported in a number of recent papers [31,[34][35][36][37][38][39]. It has been found that the reflection at the stripe edge is close to the total, |R| .…”
Section: Surface Plasmons On a Graphene Stripementioning
confidence: 97%
“…Reflection and scattering of a surface plasmon from discontinuities in the graphene plane-including the reflection from the edge of a graphene stripe-has already been studied in detail and reported in a number of recent papers [31,[34][35][36][37][38][39]. It has been found that the reflection at the stripe edge is close to the total, |R| .…”
Section: Surface Plasmons On a Graphene Stripementioning
confidence: 97%
“…Beyond geometrical edges, grain boundaries, [ 13 ] domain walls, [ 14 ] electronic barriers, [ 15 ] and gaps [ 16 ] with significant topographic mismatch or electronic state discontinuity are also intriguing polaritonic reflectors, giving rise to various reflection phenomena. [ 17 ] Therefore, to design polaritonic devices, nanocavities, and metastructures for practical applications, [ 18–20 ] it is of great necessity to understand, model, and in situ manipulate the nanoscale scattering of polaritons.…”
Section: Introductionmentioning
confidence: 99%
“…Optical Mater. 2020,8, 1902104 www.advancedsciencenews.com © 2020 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim…”
mentioning
confidence: 99%
“…The contribution by Fengrui Hu and Zhe Fei discusses the recent studies of exciton polaritons in group‐VI TMDCs. The progress report by Zhiwen Shi and co‐workers summarizes the advances on the scaling and reflection behaviors of strongly confined polaritons in three representative low‐dimensional material systems.…”
mentioning
confidence: 99%